Structural insight into the calcium ion modulated interdomain electron transfer in cellobiose dehydrogenase. Issue 11 (8th April 2015) - Kadek, Alan; Kavan, Daniel; Felice, Alfons K.G.; Ludwig, Roland; Halada, Petr; Man, Petr
Abstract : Cellobiose dehydrogenase (CDH) from wood degrading fungi represents a subclass of oxidoreductases with unique properties. Consisting of two domains exhibiting interdomain electron transfer, this is the only known flavocytochrome involved in wood degradation. High resolution structures of the separated domains were solved, but the overall architecture of the intact protein and the exact interface of the two domains is unknown. Recently, it was shown that divalent cations modulate the activity of CDH and its pH optimum and a possible mechanism involving bridging of negative charges by calcium ions was proposed. Here we provide a structural explanation of this phenomenon confirming the interaction between negatively charged surface patches and calcium ions at the domain interface. Abstract : Ca 2+ modulation of cellobiose dehydrogenase functioning was studied by H/D exchange. Sites at the domain interface influenced by the presence of Ca 2+ were elucidated. Ca 2+ binds to negatively charged patches on both domains of cellobiose dehydrogenase. These observations explain Ca 2+ mediated increase in interdomain electron transfer.